Evaluation of the effect of a Nursing System Framework on Nurse Sensitive Indicators, mortality and readmission in an NHS Trust. Issue 2 (5th October 2022) - Cannaby, Ann‐Marie; Carter, Vanda; Warren, Katherine; Gwinnett, Jason; Bailey, Karla; Mahmud, Sultan; Gray, Richard
Abstract: In 2018, an NHS Trust (UK) implemented an innovative Nursing System Framework (NSF). The NSF formalized a two‐year strategy, which provided teams with clear aims and measurable objectives to deliver care. Failures of coordination of nursing services are well‐recognized threats to the quality, safety and sustainability of care provision. Aim: To evaluate the efficacy of introducing a NSF in an NHS Trust, using nursing sensitive indicators and pre‐selected mortality, data outcome measures. Design: A before and after implementation, observational study. Methods: 105, 437 admissions were extracted at an admission record level. Data was extracted from 1st September 2018 through to the 31st August 2019. Results: Using SQUIRE guidelines to report the study, insufficient evidence was found to reject a null hypothesis with a chi‐squared test of association between in‐hospital death and the NSF intervention period, with a p ‐value of .091. However, trends were seen in the data, which suggested a positive association. Conclusion: The NSF is a complex intervention, which provides direction for improvements but requires further research to understand the benefits for nurses, Midwives, Health Visitors and patients.